RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND PRACTICE WITH APPLICATION DOCUMENTATION PARTOGRAPH BY MIDWIFERY STUDENTS OF BUNGA KALIMANTAN BANJARMASIN - Aulia Rahmi; Widya Astutik (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Partograph is one of the useful tools in monitoring the progress of labor as the recommendation of the Ministry of Health and WHO (World Health Organization) to prevent delays in handling. Midwives as caregiver and monitoring in labor must be skilled in the use of partograph. Results of preliminary study that involved 8 midwifery students of Bunga Kalimantan Banjarmasin who were observing labor,shows none of them had initiative to make partograph. Aims: The purpose of this study is to find the relationship between knowledge, attitude, and practice of midwifery students of Bunga Kalimantan Banjarmasinto the partograph documentation. Methods: This research was an analytical study with cross-sectionalapproach.There were 80 respondents of Level II Midwifery students of Bunga Kalimantan Banjarmasin selected randomly and involved in this study. Results: The result showed that the respondents has good knowledge and positive attitudes to partograph documentation, but never experienced on it. We found that there were positive correlation between the partograph documentation with students’ knowledge (p value < 0.001), attitudes (p value < 0.01), and practices (p value < 0.01). Conclusion: The data suggests that students’ knowledge and attitudes to partograph documentation are not enough to increase their initiative to make partograph during observation in labor room. Practice to the partograph documentation will higher their performance.